Accuracy and Prognosis Value of the Sequential Organ Failure Assessment Score Combined With C-Reactive Protein in Patients With Complicated Infective Endocarditis - Lin, Yaowang; Dong, Shaohong; Yuan, Jie; Yu, Danqing; Bei, Weijie; Chen, Ruimian; Qin, Haiyan (Frontiers in Medicine, 2021)
To evaluate the efficacy and prognostic value of the sequential organ failure assessment (SOFA) score combined with C-reactive protein (CRP) in patients with complicated IE. A total of 246 consecutive patients with complicated IE were included. These patients were divided into four groups depending on the SOFA score and CRP optimal cutoff values, which were determined using the receiver operating characteristic analysis: low SOFA and low CRP (n=83), low SOFA and high CRP (n=87), high SOFA and low CRP (n=25), and high SOFA and high CRP (n=51). The primary endpoints included in-hospital death, in-hospital embolic complications, and long-time mortality. High SOFA score and high CRP were associated with about 29.41% (15/51) of higher incidence of in-hospital death with an area under the curve (AUC) of 0.872. Besides, high SOFA score and high CRP were associated with higher embolic complications with an AUC of 0.759. Multivariate analyses showed that age [odds ratio (OR=2.25, 1.15–4.44)], neurological failure [Glasgow Coma Scale (GCS≤12)] (OR=2.52, 1.04–4.28), SOFA≥5 (OR=9.39, 3.64–16.89), and surgical treatment (OR=0.11, 0.03–0.34) were clinical predictors for in-hospital death. On following up for 12–36 months, SOFA≥5 (p=0.000) showed higher mortality. High SOFA score combined with increased CRP levels is significantly associated with death, and embolic complications during hospitalization, but not CRP, predict long-time mortality in complicated IE.